Is There an Association Between Metformin Exposure and Frailty?. (June 2020) - Baskaran, Dhanya; Aparicio-Ugarriza, Raquel; Ferri-Guerra, Juliana; Milyani, Raneem; Florez, Hermes; Ruiz, Jorge G.
Frailty is a state of vulnerability to stressors resulting in higher morbidity, mortality, and utilization in older adults. Frailty and type 2 diabetes mellitus share similar pathophysiological mechanisms which metformin may target. The purpose of this study was to determine whether exposure to metformin is associated with frailty in veterans. This is a cross-sectional study of veterans 65 years and older with type 2 diabetes who were screened for frailty between January 2016 and August 2017. We constructed a 44-item Frailty Index including multiple variables using a deficit accumulation framework. After adjustment for covariates, the association was calculated using binomial logistic regression models with frailty status as the outcome variable, and metformin exposure as the independent variable. Patients were 98.3% male and 56.7% White with a mean age of 72.9 ( SD = 6.8) years. The proportion of robust, prefrail and frail patients was 2.9% ( n = 22), 46.7 % ( n = 356) and 50.5% ( n = 385), respectively. In binomial logistic regression, exposure to metformin was associated with lower risk for frailty, adjusted odds ratio (OR) = .55 (95% confidence interval [CI] = .39–.77), p ≤ .001. This study shows that exposure to metformin was associated with lower risk for frailty in community-dwelling veterans.